Comparison of TFT-LCD and CRT on visual recognition and subjective preference - Chen, Ming-Te; Lin, Chin-Chiuan (International journal of industrial ergonomics, 2004)
This study investigated the effects of screen type, contrast ratio, and ambient illumination on visual recognition and subjective preference for visual display terminal (VDT) screen characteristics. Screen type and ambient illumination did not significantly affect visual recognition. The visual recognition was slightly better for 200 lx ambient illumination than for 450 and 700 lx. However, contrast ratio significantly affected visual recognition, with a higher contrast ratio resulting in better visual recognition. Subjective preference was significantly affected by screen type and contrast ratio. Subjects preferred the thin film transistor liquid crystal display (TFT-LCD) to a cathode ray tube (CRT). The subjective preference level improved as the contrast ratio increased. In conclusion, the TFT-LCD did not show significantly better visual recognition than the CRT. However, based on the analysis of the subjective ratings, the TFT-LCD may be the better choice for VDT tasks. Higher contrast ratio resulted in better visual recognition and higher subjective preference. Lower ambient illumination (200 lx) was slightly better in terms of both visual recognition and subjective preference compared to higher ambient illumination (700 lx). Screen type, contrast ratio, and ambient illumination were the key factors affecting visual recognition and the subjective preference for VDTs. The results from this study may not only improve VDT performance but also may enhance worker satisfaction given their preferences for VDT screen characteristics.